Global impact of COVID-19 on animal health and welfare - RAHMAN, H; HIREMATH, JAGADISH B; CHANDA, MOHAMMED MUDASSAR; K, VIJAYALAKSHMY; B, CHETAN KUMAR H; YOGISHARADHYA, R (The Indian Journal of Animal Sciences, 2021)
The COVID-19 pandemic is a global public health emergency that caused high scale morbidity and mortality in humans and billions got affected economically, psychologically and socially due to sudden change in lifestyle. Livestock sector involving millions of poor and marginal farmers was impacted due to movement restriction among humans. Animal health and disease management activities were delayed, halted, or abandoned due to pandemic. The industry slowed down for want of timely raw materials of livestock origin and also acute shortage of labourers due to pandemic. Though there are no estimates of economic loss incurred but indirect measures indicate significant direct and indirect losses to the sector. The animal health and disease data across world and the experience gained so far in handling pre-, post-, and during COVID-19 pandemic will provide essential inputs for preparedness to face future challenges.